Aviation Vision and the Optometrist - Hart, L.G (Canadian Journal of Optometry, 2021)
With new Federal legislation requiring the pilot to identify himself or herself as a pilot to the examining optometrist, it is important for the optometrist to have some knowledge of the flight environment. Basic optometric techniques such as visual acuity measurements, depth perception, colour vision, etc. are discussed and related to the working world of the aviator. Future cockpit designs and their affects relative to the visual systems are also discussed.